Molecular and Biochemical Characterization of a Bimodular Xylanase From Marinifilaceae Bacterium Strain SPP2 - Han, Zhenggang; Shang-guan, Fang; Yang, Jiangke (Frontiers in Microbiology, 2019)
In this study, the first xylantic enzyme from the family Marinifilaceae, XynSPP2, was identified from Marinifilaceae bacterium strain SPP2. Amino acid sequence analysis revealed that XynSPP2 is a rare Fn3-fused xylanase, consisting of a signal peptide, a fibronectin type-III domain (Fn3), and a C-terminal catalytic domain belonging to glycoside hydrolase family 10 (GH10). The catalytic domain shared 17% - 46% identities to those of biochemically characterized GH10 xylanases. Structural analysis revealed that the conserved asparagine and glutamine at the glycone -2/-3 subsite of GH10 xylanases are substituted by a tryptophan and a serine, respectively, in XynSPP2. Full-length XynSPP2 and its Fn3-deleted variant (XynSPP2∆Fn3) were overexpressed in Escherichia coli and purified by Ni-affinity chromatography. The optimum temperature and pH for both recombinant enzymes were 50oC and 6, respectively. The enzymes were stable under alkaline condition and at temperature lower than 50oC. With beechwood xylan as the substrate, XynSPP2 showed 2.8 times the catalytic efficiency of XynSPP2∆Fn3, indicating that the Fn3 module promotes xylanase activity. XynSPP2 was active towards xylooligosaccharides (XOSs) longer than xylotriose. Such a substrate preference can be explained by the unique -2/-3 subsite composition in the enzyme which provides new insight into subsite interaction within the GH10 family. XynSPP2 hydrolyzed beechwood xylan into small XOSs (xylotriose and xylotetraose as major products). No monosaccharide was detected by thin-layer chromatography which may be ascribed to putative transxylosylation activity of XynSPP2. Preferring long XOS substrate and lack of monosaccharide production suggest its potential in probiotic XOS manufacture.